2020
DOI: 10.1021/acs.jpclett.0c02624
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Based Synthesis and Host–Guest Chemistry of Plasmonic Nanogap Particles with Strong, Quantitative, and Highly Multiplexable Surface-Enhanced Raman Scattering Signals

Abstract: We developed a synthetic strategy to form cyclodextrin-based intrananogap particles (CIPs) with a well-defined ∼1 nm interior gap in a high yield (∼97%), and were able to incorporate 10 different Raman dyes inside the gap using the cyclodextrin-based host–guest chemistry, leading to strong, reproducible, and highly multiplexable surface-enhanced Raman scattering (SERS) signals. The average SERS enhancement factor (EF) for CIPs was 3.0 × 109 with a very narrow distribution of the EFs that range from 9.5 × 108 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
(61 reference statements)
0
30
0
Order By: Relevance
“…Overall, a key challenge is the ultra-precise synthesis of the targeted PGNs in a very high yield, and this could be easily translated into highly reliable and quantitative plasmonic response including SERS, as shown by various plasmonic nanogap particles formed and controlled by thiolated DNA, dealloying, silica/polymer interlayer, and host-guest chemistry. [9,15,19,27,28,34,48,54,56] While recently advanced top-down methods, such as electron-beam lithography, allow the versatile fabrication of PGNs with various morphologies, the reproducible synthesis of welldefined ultrasmall (1 nm or less) nanogaps in high yields has been mainly realized by the bottom-up approach. In particular, the high local field enhancements in ultrasmall nanogaps imply that subtle changes in this region significantly alter the plasmonic response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, a key challenge is the ultra-precise synthesis of the targeted PGNs in a very high yield, and this could be easily translated into highly reliable and quantitative plasmonic response including SERS, as shown by various plasmonic nanogap particles formed and controlled by thiolated DNA, dealloying, silica/polymer interlayer, and host-guest chemistry. [9,15,19,27,28,34,48,54,56] While recently advanced top-down methods, such as electron-beam lithography, allow the versatile fabrication of PGNs with various morphologies, the reproducible synthesis of welldefined ultrasmall (1 nm or less) nanogaps in high yields has been mainly realized by the bottom-up approach. In particular, the high local field enhancements in ultrasmall nanogaps imply that subtle changes in this region significantly alter the plasmonic response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al expanded the palette of Raman dyes for highly multiplexed sensing and imaging and incorporated 10 different within a plasmonic intragap by adopting cyclodextrin(CD)-based host-guest chemistry while forming CD-based intrananogap particles (CIPs). [48] Around 95% of the measured SERS EFs from individual CIPs were narrowly distributed between 9.5 × 10 8 to 9.5 × 10 9 with a high average EF value (3.0 × 10 9 ) due to the uniformly synthesized intragap particles with a clear gap morphology in a high yield (≈97%). It was shown that 10 different Raman dye-coded CIPs were clearly distinguishable with fingerprint SERS peaks.…”
Section: Sersmentioning
confidence: 95%
See 2 more Smart Citations
“…Typically, the metallic nanogap can generate surface plasma resonance that will strongly enhance the localized electromagnetic field. This effect has great prospects in SERS (surface enhanced Raman scattering) [ 12 , 13 , 14 , 15 ] and sensing [ 16 , 17 , 18 ]. In these application scenarios, fabricating large-area metallic nanogaps in a low-cost manner is of great importance.…”
Section: Introductionmentioning
confidence: 99%